PENGARUH KREATIVITAS MENGAJAR GURU TERHADAP MOTIVASI BELAJAR MASA PANDEMI - Taufiq Tsany Mahmud; Jonet Ariyanto Nugroho; Khresna Bayu Sangka (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2022)
This research aims to determine the effect of teacher creativity on the learning motivation. This research is a descriptive quantitative with the pupulation is student from SMKN in Sukoharjo regency. The number of sample was 343 student. Sampling technique this research collected the data questionnaire, the data analyzed simple linier regression analysis. The results revealed that teacher creativity has a positive and significant impact which shown from the T value (7,229) is greater than the T table (2,251). The result of R square show that teacher creativity affects 13,3% of student learning motivation, while the rest is affected by others factors.